The application of blended learning methods to enhance cognitive function and self-efficacy - Fasiroka, Ema Yulia; Nasrulloh, Ahmad; Visalim, Aqim; Salman, Muhammad (Universitas Negeri Yogyakarta, 2025)
This study aims to evaluate the improvement of cognitive function and self-efficacy among students through the application of blended learning methods. This classroom action research (CAR) was conducted in two cycles, with each cycle including planning, implementation, observation, and reflection stages. The subjects of the study were 36 students from class X MIPA 5 at SMA Negeri 2 Wonogiri. Cognitive function data were collected using cognitive tests, while self-efficacy data were gathered through a self-efficacy scale questionnaire. The results showed that the application of blended learning methods effectively improved students' cognitive function. Before the intervention, the average cognitive score of students was 59.0%, which increased to 66.8% after the first cycle and reached 76.8% after the second cycle. The most significant improvements were observed in the dimensions of analysis and evaluation skills, with the average score increasing from 58.0% to 76.0% for analysis, and from 55.5% to 73.5% for evaluation after two cycles. Additionally, students' self-efficacy also showed significant improvement, with 30% of students at a high level, 68% at a moderate level, and only 2% at a low level after the second cycle. This study concludes that the blended learning method not only enhances students' overall cognitive abilities but also strengthens their confidence in tackling academic tasks.